2001
DOI: 10.1046/j.1365-2133.2001.04448.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQB1 alleles in Italian patients with mucous membrane pemphigoid predominantly affecting the oral cavity.

Abstract: Our data suggest that Italian patients with MMP lesions predominantly affecting the oral cavity present the same genetic predisposition linked to HLA-DQB1*0301 previously reported mainly in patients with OCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 14 publications
0
16
0
2
Order By: Relevance
“…Penfigóide cicatricial ocular (PCO), variante do pênfigo membrano-mucoso (PMM) (32) , é uma doença auto-imune que forma bolhas e cicatrizes em conjuntiva, podendo causar perda da visão quando inadequadamente tratada (13) . Em caucasianos, os haplótipos HLA-DR4-DQw7 e -DR5-DQw7 (13) , especialmente o alelo HLA-DQB1*0301 (13,(33)(34)(35)(36) , são tidos como marcadores genéticos para essa doença.…”
Section: Penfigóide Cicatricial Ocularunclassified
“…Penfigóide cicatricial ocular (PCO), variante do pênfigo membrano-mucoso (PMM) (32) , é uma doença auto-imune que forma bolhas e cicatrizes em conjuntiva, podendo causar perda da visão quando inadequadamente tratada (13) . Em caucasianos, os haplótipos HLA-DR4-DQw7 e -DR5-DQw7 (13) , especialmente o alelo HLA-DQB1*0301 (13,(33)(34)(35)(36) , são tidos como marcadores genéticos para essa doença.…”
Section: Penfigóide Cicatricial Ocularunclassified
“…18 Both BP and MMP have been shown to have a strong linkage to DQB1*0301. 18,19 It has been demonstrated that the same patient may have antibodies against more than one autoantigen within the skin and mucous membrane, resulting in more than one autoimmune mucocutaneous disease. For example, patients with PF may develop BP, 20,21 patients with MMP may have PV (22), and some patients are affected with both PV and OCP.…”
Section: Introductionmentioning
confidence: 99%
“…HLA-DQB1*0301 allele, associated with MMP [111][112][113][114], was reported in patients with esophageal squamous cell carcinoma [113], gastric cancer [115], HPV-associated cervical neoplasia [116]. It was hypothesized, that the gene may have a role in T-cell recognition of basement membrane antigens resulting in production of IgG autoantibodies binding basement membrane antigens [117].…”
Section: Genetic Predispositionmentioning
confidence: 99%